Modeling of the straw tube tracker for the COMET experiment - Shoukavy, Dzmitry V.; Leonau, Aliaksandr V.; Feranchuk, Ilya D.; Anishchik, Victor M.; Ponariadov, Vladimir V.; Evtoukhovitch, Petr G. (Journal of the Belarusian State University. Physics, 2017)
In the present paper a parametric model of a straw tracker is implemented on the basis of technical design report of the COMET experiment within the Geant4 toolkit. This model allows one to smoothly tailor both the diameter and width of the film and to vary the gas mixture. In order to investigate the response of the straw detector to the propogation of the charged particles, a «physical sheet» corresponging to the COMET conditions (i. e. a set of all possible processes for all participating particles defining the interaction in the Geant4) is created. We show that it is impossible to reach high accuracy in identification of the particles solely on the basis of the data obtained within the straw tracker because, depending on the threshold energy, false identification is liable when a muon or pion is treated as an electron. The optimum mixture of gases for the straw tracker within the conditions of the Phase-II of the COMET experiment is obtained on the basis of Monte-Carlo modeling for the propagation of charged particles (electrons, pions and muons) with 105 MeV/c momentum through a system of 5 straw modules. It is shown that, as regards the momentum reconstruction error, the mixture He – C2H6 is an optimum mixture of gases among all the candidates possible (Ar – C2H6, He – C2H6, Xe – C2H6 in the proportion 50 : 50).